Increasing Multidrug Resistance in Helicobacter pylori Strains Isolated from Children and Adults in Mexico - Torres, Javier (American Society for Microbiology, 2001)
The susceptibilities to three antimicrobials of 195 Helicobacter pylori strains isolated from Mexican patients is reported; 80% of the strains were resistant to metronidazole, 24% were resistant to clarithromycin, and 18% presented a transient resistance to amoxicillin. Resistance to two or more antimicrobials increased significantly from 1995 to 1997.